Probing Light: Projection Mapping, Architectural Surface, and the Politics of Luminous Abstraction - Korola, Katerina (Intermédialités / Intermediality, 2014)
Over the last decade, 3D projection mapping has flourished around the world under the auspices of corporate publicity firms, arts organizations, and urban-branding initiatives. In the popular press, this work has been hailed at once as fulfilling the ambitions of expanded cinema (freeing the moving image from the screen) and as performative architecture (liberating architecture from stasis). However, this emphasis on the freedom of the moving image, on the one hand, and on movement itself, on the other, has caused neglect toward the way that such projections interact with their architectural support. Indeed, in its short history, projection mapping has already developed favoured idioms, whose repetition across the globe draws into question its site-specificity. Whereas unapologetically commercial projects have tended toward figurative motifs, projects aspiring to the artistic have tended to systematically favour the language of abstraction. This latter group is the concern of this essay, in which, drawing on the critical framework provided by earlier inter-war debates surrounding light architecture, the author investigates the potential and limitations of such luminous abstractions in engendering new forms of spatial experience. Do these high-tech projections encourage the spectator to engage with architecture in a new way, or do they instead efface their architectural setting beneath an ornamental visual spectacle?